The Effect Of Black Tea (Camellia sinensis) Administration On Renal Histopathology Of Male White Rats (Rattus norvegicus) From Sprague Dawley Strain Induced By Used Cooking Oil - Hilda Taurina; Jihan Vira Yuniar; Elvira Yunita (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2021)
Used cooking oil is cooking oil that has been heated repeatedly, so that it can cause the formation of free radical compounds. Free radicals are toxic kidneys that generate cell injury via lipid peroxidation, DNA damage, and protein peroxidation. Black tea (Camellia sinensis) infusion has a strong polyphenol group, namely epigallocatechin gallate, thearubigin, theaflavin, the amino acid L-theanine, flavonols, and catechins that can inhibit free radicals and protect organs from oxidative stress. This study was a post-only control group design experiment. The research subjects used were 24 Sprague Dawley male rats which were divided into six groups. The first group was the control group (K0). Treatment group 1 was given distilled water and used cooking oil after 12 times heating (K1), treatment group 2 was given black tea at a dose of 2.5g/ kg bw (body weight) and distilled water (K2), and treatment group 3 was given black tea at a dose of 3.75 g/kg bw and distilled water (K3). Treatment group 4 was given used cooking oil after 12 times heating and black tea with a dose of 0.50 gr/200 gr bw (K4), treatment group 5 was given used cooking oil after 12 times heating and black tea with a dose of 3.75 g/kg bw (K5). All groups were treated for 42 days. Then, the rats' kidney was collected, and data were analyzed by Kruskal Wallis and One Way ANOVA test. The results of the Kruskal Wallis and One Way ANOVA test showed a decrease in glomerular and tubular damage after the rats orally induced with black tea were given 12x heating used cooking oil (p<0.05). The mean histopathological score in the administration of black tea at a dose of 3.75 g/kg bw was lower than at a dose of 2.5 g/kg bw. This study shows that infusion of black tea (Camellia sinensis) can prevent glomerular and tubular damage induced by used cooking oil.